Pushover Analysis of Reinforced Concrete Frame - Bansal, Rohit (My University, 2011)
To model the complex behaviour of reinforced concrete analytically in its non-linear zone is difficult. This has led engineers in the past to rely heavily on empirical formulas which were derived from numerous experiments for the design of reinforced concrete structures. For structural design and assessment of reinforced concrete members, the non-linear analysis has become an important tool. The method can be used to study the behaviour of reinforced concrete structures including force redistribution. This analysis of the nonlinear response of RC structures to be carried out in a routine fashion. It helps in the investigation of the behaviour of the structure under different loading conditions, its load deflection behaviour and the cracks pattern. In the present study, the non-linear response of RCC frame using SAP2000 under the loading has been carried out with the intention to investigate the relative importance of several factors in the non-linear analysis of RCC frames. This include the variation in load displacement graph.
M.E. (Structures)
Keywords: Concrete; Reinforced Concrete